2023
DOI: 10.1111/pace.14839
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vein isolation by means of a novel cryoballoon technology in paroxysmal atrial fibrillation patients: 1‐year outcome from a large Italian multicenter clinical registry

Stefano Bianchi,
Antonio De Simone,
Saverio Iacopino
et al.

Abstract: IntroductionRecently, a new cryoballoon (CB) technology (POLARx; Boston Scientific) has come onto the market. Preliminary data have shown that its acute safety and efficacy are similar to those of the first‐generation CB. The aim of this study was to assess the medium‐term outcome of pulmonary vein isolation (PVI) with the POLARxTM CB in a large multicenter registry.MethodsWe prospectively collected data on 125 consecutive patients with paroxysmal atrial fibrillation (AF) who underwent PVI by means of a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…12 At present there is limited long-term (1 year) outcome data on this novel cryoballoon, and little data available on the safety or effectiveness of the novel variable size cryoballon. 12 While multiple studies have reported both acute procedural data, [13][14][15][16] and chronic 1 year outcomes, [17][18][19] only a few reports of large patient cohorts exist. 13,14,18,20,21 FROZEN AF is an international multicenter, open-label, prospective, single-arm study to determine the safety and performance of a novel cryoballoon system for treatment of PAF, additionally an extension arm examined the safety and performance of a novel variable size cryoballon.…”
Section: Introductionmentioning
confidence: 99%
“…12 At present there is limited long-term (1 year) outcome data on this novel cryoballoon, and little data available on the safety or effectiveness of the novel variable size cryoballon. 12 While multiple studies have reported both acute procedural data, [13][14][15][16] and chronic 1 year outcomes, [17][18][19] only a few reports of large patient cohorts exist. 13,14,18,20,21 FROZEN AF is an international multicenter, open-label, prospective, single-arm study to determine the safety and performance of a novel cryoballoon system for treatment of PAF, additionally an extension arm examined the safety and performance of a novel variable size cryoballon.…”
Section: Introductionmentioning
confidence: 99%
“…11 Additionally, a second generation of this novel cryoballoon that allows inflation and ablation at 2 sizes, 28mm or 31mm, has also become available. 12 At present there is limited long-term (1yr) outcome data on this novel cryoballoon, and little data available on the safety or effectiveness of the novel variable size cryoballon 12 While multiple studies have reported both acute procedural data, [13][14][15][16] and chronic 1 year outcomes, [17][18][19] only a few reports of large patient cohorts exist. 13,14,18,20,21 FROZEN AF is an international multi-center, open-label, prospective, single-arm study to determine the safety and performance of a novel cryoballoon system for treatment of PAF, and an extension arm which examined the safety and performance of a novel variable size cryoballon.…”
Section: Introductionmentioning
confidence: 99%